Storytelling untuk mengurangi perilaku agresi pada anak - Jeng Nita Miswartiningsi (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Aggression is any form of behavior that is intended to hurt someone physically or psychologically. The behavioral characteristics are based on several aspects, namely aspects of physical aggression, verbal, anger and hostility. Subject (female / 9 years) has a problem of aggressive behavior. The assessments used were clinical interviews, observations, psychological tests (CAT and CPM). The results showed that the subject carried out aggressive behavior as a result of the learning process modeling from his father, and followed the same behavioral response in order to get the wants and needs desired. The intervention given uses storytelling to reduce aggressive behavior in children. The results obtained that storytelling can effectively reduce aggressive behavior in children.